Dopamine depletion reduces food-related reward activity independent of BMI - Frank, Sabine; Friederich, Hans-Christoph (Neuropsychopharmacology, 2016)
Reward sensitivity and possible alterations in the dopaminergic-reward system are associated with obesity. We therefore aimed to investigate the influence of dopamine depletion on food-reward processing. We investigated 34 female subjects in a randomized placebo-controlled, within-subject design (body mass index (BMI)=27.0 kg/m2 ±4.79 SD; age=28 years ±4.97 SD) using an acute phenylalanine/tyrosine depletion drink representing dopamine depletion and a balanced amino acid drink as the control condition. Brain activity was measured with functional magnetic resonance imaging during a ‘wanting’ and ‘liking’ rating of food items. Eating behavior-related traits and states were assessed on the basis of questionnaires. Dopamine depletion resulted in reduced activation in the striatum and higher activation in the superior frontal gyrus independent of BMI. Brain activity during the wanting task activated a more distributed network than during the liking task. This network included gustatory, memory, visual, reward, and frontal regions. An interaction effect of dopamine depletion and the wanting/liking task was observed in the hippocampus. The interaction with the covariate BMI was significant in motor and control regions but not in the striatum. Our results support the notion of altered brain activity in the reward and prefrontal network with blunted dopaminergic action during food-reward processing. This effect is, however, independent of BMI, which contradicts the reward-deficiency hypothesis. This hints to the hypothesis suggesting a different or more complex mechanism underlying the dopaminergic reward function in obesity.
published online 4 November 2015
Gesehen am 30.10.2019